2003
DOI: 10.1097/00000539-200302000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Declining Proportion of Publications by American Authors in Major Anesthesiology Journals

Abstract: A decline in the proportion of articles published by American authors in medical journals has been reported. We therefore sought to determine whether the contributions of authors from the United States to the three leading anesthesia journals changed between the years 1980 to 2000. The journals Pain, Anesthesiology, and Anesthesia & Analgesia were selected for evaluation on the basis of their respective impact factors. All clinical studies and basic science studies published in the years 1980, 1985, 1990, 1995… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
4
9
0
1
Order By: Relevance
“…Potential causes, notably inadequate funding, have been raised in . Similar concerns have been expressed regarding a decline in randomised controlled trials from Canadian departments [4] and in contributions to anaesthesia journals from departments in the United States [3,10,11] and these results are also consistent with our data. These authors have suggested shortages of anaesthesia providers, lack of research time for anaesthetists and a lack of formalised research programs for trainees in anaesthesia as contributory factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Potential causes, notably inadequate funding, have been raised in . Similar concerns have been expressed regarding a decline in randomised controlled trials from Canadian departments [4] and in contributions to anaesthesia journals from departments in the United States [3,10,11] and these results are also consistent with our data. These authors have suggested shortages of anaesthesia providers, lack of research time for anaesthetists and a lack of formalised research programs for trainees in anaesthesia as contributory factors.…”
Section: Discussionsupporting
confidence: 91%
“…A decade ago, previous research analysed the proportion of publications that were produced by different countries in highly cited anaesthesia journals and found that high-income countries, in particular the United States, dominated global anaesthesia publications [2]. However, several groups of investigators have expressed concern that the relative contributions of the United States, the United Kingdom and Canada have diminished [1,3,4].…”
mentioning
confidence: 99%
“…2 Aux États-Unis, on est préoccupé par le déclin de la proportion de publications par les auteurs américains dans les revues d'anesthésie. 3 Au Canada, notre rôle pédagogique fait en sorte que notre position est assurée. Les départements universitaires d'anesthésie du Royaume-Uni envient la responsabilité que les départements canadiens se sont donnée pour l'enseignement doctoral et postdoctoral.…”
Section: Resultsunclassified
“…Such a trend has been observed for example in the field of anesthesiology [21], reproductive medicine [22], in clinical-research journals [23] and in surgical journals [24,25]. This relative reduction is research productivity reflects the increasing participation of Western European (mainly the United Kingdom, some Scandinavian countries and the Netherlands) countries to the field of bioethics.…”
Section: Discussionmentioning
confidence: 97%